PEMAKNAAN KHALAYAK TERHADAP REPRESENTASI FATHERHOOD DALAM FILM NANTI KITA CERITA TENTANG HARI INI - Khoirunnisa Nur Fithria; Hapsari Dwiningtyas Sulistyani; Primada Qurrota Ayun (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Father's dominance in the family and parenting spheres often leads to conflicts as violence, oppression, and even trauma due to an imbalance roles between fathers and mothers. The issue of fatherhood also appears in the film NKCTHI as a representation of the social reality brought by the filmmakers. With the reception study, the researcher focuses on the interaction between the Z generation audience and the texts that appear in the media so that a picture emerges of how the media is able to influence or not influence the audience in defining the social reality related to fatherhood that appears in the film. Based on these problems, this study aims to determine the position of the audience's reception of the representation of fatherhood in the film Later Kita Stories About Today based on the three positions of Hall's meaning, namely : dominant reading, negotiation reading, and oppositional reading. This study uses a critical paradigm with Stuart Hall's encoding-decoding theory, muted groups, and libertarian radical feminism. There are 6 scenes chosen to see the meaning, such as: (1) Father's attitude in making decisions, (2) Father's communication with his partner, (3) Father's protection efforts, (4) Father's protective attitude, (5) Domestic activities carried out Father, (6) The attitude of the father in explaining to his child. The results showed that the audience's meaning was influenced by various factors such as family conditions, gender identity, consumption of other media, knowledge related to gender, the context of the scene in the film, and personal opinions regarding the social conditions. Although the meanings appear in various receptions, the results of the study show that the majority of informants are still in a dominant position. All male informants and 1 female informant are mostly in dominant positions, while the other two female informants are mostly in negotiating and opposition positions. The reception of informants is still influenced by patriarchal ideology and masculine ways of thinking in interpreting fatherhood in the film. Although there are also feminine thoughts and awareness of gender roles in some scenes, their receptions do not completely leave the patriarchal mindset.